Income and democracy: a comment on Acemoglu, Johnson, Robinson, and Yared (2008) - Erich Gundlach; Martin Paldam (Kiel Institute for the World Economy (IfW), 2008)
Acemoglu, Johnson, Robinson, and Yared (2008) demonstrate that estimation of the standard adjustment model with country-fixed and time-fixed effects removes the statistical significance of income as a causal factor of democracy. We argue that their empirical approach must produce insignificant income effects and that a small change in the estimation process immediately reveals the strong effect of income on democracy.
Keywords: D72; O43; 330; Democracy; modernization hypothesis; fixed-effects estimation; Einkommen; Sozialprodukt; Demokratie; Schätztheorie